Inside Front Cover: Self‐assembled organic/metal ion nanohybrids for theranostics (View 2/2020). Issue 2 (26th June 2020) - Zhang, Kai; Zhao, Nana; Xu, Fu‐Jian
Abstract : In article number 17, Fu‐Jian Xu and co‐workers demonstrate that self‐assembled organic/metal ions nanohybrids composed of designable organic blocks and multifarious metal ions via coordinated connection have a great potential for cancer theranostics, due to their remarkable physicochemical properties and favorable biological capacities. In the review, the authors introduce the design and fabrication of organic/metal ions nanohybrids, as well as their applications in biosensing, bioimaging, treatments and bioimaging‐guided therapy of cancers.